Stress amplifies memory for social hierarchy - Cordero, María I.; Sandi, Carmen (Frontiers in Neuroscience, 2007)
Individuals differ in their social status and societies in the extent of social status differences among their members. There is great interest in understanding the key factors that contribute to the establishment of social dominance structures. Given that stress can affect behavior and cognition, we hypothesized that, given equal opportunities to become either dominant or submissive, stress experienced by one of the individuals during their first encounter would determine the long-term establishment of a social hierarchy by acting as a two-stage rocket: (1) by influencing the rank achieved after a social encounter and (2) by facilitating and/or promoting a long-term memory for the specific hierarchy. Using a novel model for the assessment of long-term dominance hierarchies in rats, we present here the first evidence supporting such hypothesis. In control conditions, the social rank established through a first interaction and food competition test between two male rats is not maintained when animals are confronted 1 week later. However, if one of the rats is stressed just before their first encounter, the dominance hierarchy developed on day 1 is still clearly observed 1 week later, with the stressed animal becoming submissive (i.e., looser in competition tests) in both social interactions. Our findings also allow us to propose that stress potentiates a hierarchy-linked recognition memory between “specific” individuals through mechanisms that involve de novo protein synthesis. These results implicate stress among the key mechanisms contributing to create social imbalance and highlight memory mechanisms as key mediators of stress-induced long-term establishment of social rank.